The effect of The Addition of Several Various Natural Preservatives and Their Concentration on Changes in the Quality of Arenga pinnata Sap - Parulian Soritua; Sentosa Ginting; Herla Rusmarilin (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The aim of this essential is to determine the effect of adding of several natural preservatives and their concentration on the quality of Arenga pinnata sap. The research had been performed using factorial Completely Randomized Resign (CRD) with two factors, i.e; the natural preservative (B) : (mangosteen fruit skin, guava leaves, tea leaves) and the concentration of natural preservatives (K) : (1%, 3%, 5%, and 7%). Parameters analyzed were pH, viscocity,  ash content, total acid, total sugar, total dissolved solids, and organoleptic values (colour, aroma and taste,). The result of this research showed that the natural preservativeshad highly significant effect on all parameters. The concentration of natural preservatives had highly significant effect on all parameters. The interaction of the natural preservative and their concentrationhad significant effect onpH, viscocity, total acid, organoleptic aroma and taste, but had no significant effect on ash content, total sugar, total dissolved solids, and colour. The natural preservative mangosteen fruit skinand concentration of natural preservatives of 7% had the best result on quality of Arenga pinnata sap. Keywords :  Arenga pinnata sap, natural preservative , mangosteen, viscocity.